1983
DOI: 10.1111/j.1755-3768.1983.tb01474.x
|View full text |Cite
|
Sign up to set email alerts
|

Long Term Results of Corneal Grafting in Keratoconus

Abstract: Fifty-four corneal grafts in 45 keratoconus patients have been followed for 3 to 12 years (average 5.8 years). The corneal clarity, visual acuity, incidence of immune rejections, relation to HLA compatibility, corneal thickness and endothelial cell density are reported. At the follow-up 98% (53 out of 54) of the grafts were clear. Visual acuity was greater than or equal to 0.67 in 72% of the cases. Suboptimal vision was due to cataract or large astigmatism. Rejection had occurred in 5 cases (10%). The graft th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
5
0
1

Year Published

1984
1984
2012
2012

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(9 citation statements)
references
References 15 publications
3
5
0
1
Order By: Relevance
“…The cause of graft failure deserves special consideration: only 3 cases of permanent oedema developed due to rejection episodes, which were detected in a total of 5 cases (15%). This frequency is comparable to the incidence of graft rejections in keratoconus (Ehlers & Olsen 1983) and in other series reported (Sautter et a]. 1972;Abbott & Forster 1979).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The cause of graft failure deserves special consideration: only 3 cases of permanent oedema developed due to rejection episodes, which were detected in a total of 5 cases (15%). This frequency is comparable to the incidence of graft rejections in keratoconus (Ehlers & Olsen 1983) and in other series reported (Sautter et a]. 1972;Abbott & Forster 1979).…”
Section: Discussionsupporting
confidence: 91%
“…A similar course was found in keratoconus grafts (Ehlers & Olsen 1983). This transient thinning might be due to a small loss of stromal tissue which has been damaged during the surgery.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Although the reported incidence of endothelial rejection episodes after PK in keratoconus varies widely from 3.6% to 31%, allograft survival at 5 to 12 years has been consistently reported to be greater than 90%. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] Occurrence of endothelial rejection episodes in our series (6.8%, 102 eyes; mean follow-up, 5.5 years) was similar to that noted by Lim et al 5 follow up, 2 years) noted a much higher rejection episode rate of 21% and 31%, respectively. Whether the proportion of cases with hydrops or ocular allergy was higher in the latter 2 studies is not known.…”
Section: Discussionsupporting
confidence: 89%
“…2,3 However, poor vision because of central corneal scarring or contact lens intolerance necessitates a penetrating keratoplasty (PK) in 20% to 59% of patients. [2][3][4] Among the numerous studies that have reported the long-term outcomes of PK in keratoconus, [5][6][7][8][9][10][11][12][13][14][15][16][17][18] only two previous studies have explored the association between corneal hydrops and allograft rejection/survival but with conflicting results. 3,4 Although Tuft et al 3 noted that eyes with resolved hydrops had significantly higher chances of endothelial rejection episodes compared with those without hydrops (20% vs. 5%; P = 0.02), Akova et al 4 noted fewer allograft rejection episodes in the hydrops group (6% vs. 11%; P = 0.7).…”
mentioning
confidence: 99%